The importance of incentives in influencing private retirement saving: Known knowns and known unknowns - Richard Blundell; Carl Emmerson; Matthew Wakefield (Institute for Fiscal Studies (IFS), 2006)
We summarise what economic theory predicts about how retirement savings decisions are affected by marginal withdrawal rates created by the tax, tax credit and benefit system, and by the information individuals are provided with. All these predictions vary across individuals with their circumstances. In documenting the incentives to save in a private pension provided by the tax, tax credit and benefit system we show that some individuals face a very strong incentive to place funds in a private pension at particular times during their working lives. Those who are basic rate taxpayers who expect to become higher rate taxpayers or move onto the taper of the Working Tax Credit have an incentive to delay making any private pension contributions until that time, while those expecting to move off that taper have an incentive to bring forward future pension contributions. When examining retirement saving it is important to consider both saving decisions and also the choice of retirement age. We cite previous evidence that both of these margins have been adjusted by individuals in the light of changed financial incentives. In particular there is evidence that spending by working age individuals was increased in the light of the introduction of the State Earnings-Related Pension Scheme. In addition evidence from West Germany and the United States shows that individuals' retirement ages can be affected substantially by changing financial incentives. There is less evidence of reduced spending by working age individuals in the light of the decision to index the Basic State Pension in line with prices rather than the greater of prices or earnings. New evidence from the English Longitudinal Study of Ageing shows that it is low and high wealth individuals who are most likely to be out of the labour market prior to the State Pension Age, though often for very different stated reasons. This suggests that if retirement incomes of those with low wealth are to be increased then increased labour market participation is perhaps a margin for them to adjust. Incentives to work and save are potentially affected by two recent UK reforms: the introduction of the two new tax credits (Working Tax Credit and Child Tax Credit) and the introduction of the Pension Credit. We present some preliminary evidence on whether the strong incentive to contribute to a private pension provided by the two new tax credits has boosted private pension participation, the results of which are somewhat inconclusive and are worthy of further research. Examining the distribution of current pensioner incomes with respect to the incentives induced by the Pension Credit reform we find that many single pensioners will see an unambiguous increase in the incentive to increase their private retirement income - for example through increased saving or later retirement. There are still large numbers of single pensioners who see a reduction in the incentive to increase their retirement income, the majority of whom have private income which they might decide to reduce. Fewer individuals in pensioner couples are eligible for the Pension Credit. Despite this we find that a similar proportion faces a reduced incentive to acquire greater income as we did for single pensioners. If the expectations of individuals do not reflect the current rules of the system, then we cannot expect to observe responses fully in line with economic theory that is predicated on full information. Recent evidence from the English Longitudinal Study of Ageing suggests that on average individuals underestimate their longevity and overestimate the private pension income that they can expect to receive. On the other hand, expectations of being in paid employment at older ages are, on average, similar to the current proportions of older individuals who are in paid work and individuals' expectations of remaining in the labour market at older ages appear to square up with the marginal financial incentives to remain in work that are created by different types of pension scheme.
Keywords: 330